Universiti Malaysia Pahang and Ningxia University Partnership Exposes Students to Intelligent Technologies - Irene, Wei Kiong Ting (2018)
As a part of our internationalization initiatives, the Faculty of Mechanical Engineering, Universiti Malaysia Pahang (UMP), Malaysia collaborates with different international higher education institutions worldwide to conduct mobility projects for not only its staff, but also students. Specifically, the faculty is working diligently to increase the number of inbound and outbound students. Besides, the faculty is also striving to embrace diverse participating institutions from various countries, bringing together a blend of cultures into learnings. In 2018 alone, the faculty has received a total of 22 inbound students from China, Indonesia, and Germany.